Pengaruh samping aplikasi deltametrin terhadap Artropoda predator penghuni permukaan tanah di pertanaman kedelai - I Wayan Winasa; Aunu Rauf (Jurnal Entomologi Indonesia, 2005)
Side Effects of Deltamethrin Application to The Ground Surface Dwelling Predatory Arthropods on Soybean Field. Side effects of deltamethrin to the ground surface dwelling predatory arthropods were studied on soybean field in Cianjur during July to October 1998. Insecticide was applied 1-4 times. Predator abundance was observed by setting pitfall traps. The results showed that application of deltamethrin reduced the abundance of ground-surface predatory arthropods, especially lycosid and linyphiid spiders, carabid beetle and formicid. Reductions of predator abundance on the plots treated with deltamethrin were around 35% to 41%. There was no significant difference on the predator abundance among the plots treated with the insecticide at difference frequencies. Observations after application showed that predator abundance on the treated plots recovered one week after application. Deltamethrin application to the soybean with dense crown (38 and 52 days after planting) did not reduce predator abundance, especially within three day range after application. However, negative effects of deltamethrin application at early vegetative growth stage (10 days after planting) on the reduction of predator abundance continued by harvesting. The abundance of detritivorous arthropods was not affected by deltamethrin application.